Alterations in Muscle Architecture: A Review of the Relevance to Individuals After Limb Salvage Surgery for Bone Sarcoma - Nelson, Christa M.; Marchese, Victoria; Rock, Kelly; Henshaw, Robert M.; Addison, Odessa (Frontiers in Pediatrics, 2020)
Osteosarcoma and Ewing’s sarcoma are the most common primary bone malignancies affecting children and adolescents. Optimal treatment requires a combination of chemotherapy and/or radiation along with surgical removal when feasible. Advances in multiple aspects of surgical management have allowed limb salvage surgery (LSS) to supplant amputation as the most common procedure for these tumors. However, individuals may experience significant impairment after LSS, including deficits in range of motion and strength that limit function and impact participation in work, school, and the community, ultimately affecting quality of life. Muscle force and speed of contraction are important contributors to normal function during activities such as gait, stairs, and other functional tasks. Muscle architecture is the primary contributor to muscle function and adapts to various stimuli, including periods of immobilization-protected weight-bearing after surgery. The impacts of LSS on muscle architecture and how adaptations may impact deficits within the rehabilitation period and into long-term survivorship is not well-studied. The purpose of this paper is to 1) provide relevant background on bone sarcomas and LSS, 2) highlight the importance of muscle architecture, its measurement, and alterations as seen in other relevant populations and 3) discuss the clinical relevance of muscle architectural changes and the impact on muscle dysfunction in this population. Understanding the changes that occur in muscle architecture and its impact on long-term impairments in bone sarcoma survivors is important in developing new rehabilitation treatments that optimize functional outcomes.